Anthropometric nutritional assessment of children followed up by Primary Care (Research, Society and Development, 2022)
Objective: to evaluate the nutritional status of children as well as to list factors associated with the investigated health condition. Method: cross-sectional study, developed in seven Family Health Strategies - ESF's in a region in the middle north of the state of Mato Grosso, Brazil. The nutritional profile was evaluated according to the weight-for-age, height-for-age and weight-for-height indexes (n = 66), with the help of the WHO Anthro program, and a questionnaire was applied to the legal representative, in order to outline the socioeconomic profile, with association estimated by applying Pearson's association test. Results: there was an inadequate nutritional status in children, with a higher rate of overweight or obesity, for females and children under 3 years of age. Conclusion: it points to a nutritional imbalance among children, which is an ascending public health problem, and a great challenge for primary care in promoting healthy eating habits from childhood.